Aqueous ozone sanitization of whole peeled onion: Process optimization and evaluation of keeping quality during refrigerated storage. (November 2021) - Aslam, Raouf; Alam, Mohammed Shafiq; Singh, Sandhya; Kumar, Satish
Abstract: Fruits and vegetables, especially in their minimally processed form, are highly susceptible to microbial spoilage, highlighting the need of a safe and effective sanitizing agent to extend their shelf-life. This study was carried out to optimize the aqueous ozone sanitization parameters viz. ozone concentration (1–5 mg/L), exposure time (2–8 min), and pH (3–5) for whole peeled onion. Consequently, the keeping quality was investigated for ozonated (optimized conditions), chlorinated (100 mg/L) and water-washed samples packed in tray packs and stored under refrigerated conditions (5±1 °C, 90 ± 1 % RH). Numerical optimization using the 3 factor, 3 level, Box and Behnken design suggested that aqueous ozone at 4.51 mg/L exposed to the onions for 8 min at a pH of 3 provided optimized sanitization that resulted in the most favorable reductions in microbial load (3.74 log CFU/g), pyruvate content (14.2 % less than fresh untreated) and a good overall acceptability score (8.5). After storage, the microbial shelf life obtained from optimized ozone sanitization was found to be 14.3 % (2 d) higher than water-washed and 13.04 % lower than chlorinated samples. Ozone-treated onion was observed to retain better quality attributes in terms of pyruvate content, color change and firmness as compared to other treatments studied. Graphical abstract: Image 1 Highlights: Optimization of ozonation for peeled onion and effects on keeping quality have been investigated. Aqueous O3 at 4.5 mg/L for 8 min at a pH of 3 was the optimum condition of sanitization. O3 extended the shelf life of peeled onion by 14 % as compared to water washing. O3 treated onion samples recorded better quality than chlorinated samples during storage.